Arthur O'Connor - Drawn from life in Maidstone Jail. - (:unkn) unknown (Atkin, J., 1798)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Maidstone Prison; O'Connor, Arthur, 1763-1852 -- Portraits; United Irishmen